Pneumonia-related infiltration of the pericardium mimics pericardial effusion, with an echocardiographic finding, surgical result, and outcome - Abdijalil Abdullahi Ali; Nazan Bitir; Ahmed Omar Mohamed; Ali Abdulkadir Ali Siyad; Mohamed Omar Hassan; Said Abdirahman Ahmed (Elsevier, 2022)
The pericardial sac in a healthy person holds 15-50 mL (mL) of serous fluid.Pericardial effusion (PE) is caused by an abnormal buildup of pericardial fluid in the space around the heart.We present here a 2-year-old healthy child who presented with shortness of breath, fever, and poor feeding for 2 days. Based on echocardiography and following the patient's condition detoriation, the patient was taken to the operation theater. Massive infiltration like substances were seen in the pericardial space instead of suspected pericardial effusion and the sample was sent to the pathology center.The child was extubated on day three postoperatively while serial lab tests, echocardiography, and chest x-ray follow-up demonstrated significant improvement.Follow up 1 week and 3 months later, the child's chest x-ray, inflammatory markers lab test, and echocardiography were normal.